anonymous
  • anonymous
1. Consider an infinite square well of width 2L centered at x = 0; i.e., V(x) =  for x  -L V(x) = 0 for –L < x < L V(x) =  for x  L a) Using the general solution,y(x) = Asin kx + Bcos kx , for an infinite square well, find the normalized ground state wave function 1(x) and its energy E1. b) Repeat part (a) for the first excited state 2(x). 2.
Physics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
@Jemurray3
anonymous
  • anonymous
The Schrodinger equation for the infinite square well is \[ -\frac{\hbar^2}{2m} y''(x) = E y(x)\] or \[y''(x) = \frac{2mE}{\hbar^2}y(x) = -k^2y(x)\] where \[k = \sqrt{\frac{2mE}{\hbar^2}} \] As mentioned in the problem, the most general solution to this problem is \[y(x) = A \sin(kx) + B\cos(kx) \] where A and B are constants that we haven't found yet. From here, we must apply our boundary conditions. From the fact that the potential is infinite outside of the well, it must be that y(-L) = y(L) = 0: \[y(-L) = A \sin(k\cdot -L) + B\cos(k\cdot L) =-A\sin(k\cdot L) + B\cos(k \cdot L) \] since sin(-x) = -sin(x) and cos(-x) = cos(x). Also, at x= L, \[y(L) = A\sin(k\cdot L) + B\cos(k \cdot L) \] Notice for this to be true, A must be zero because there's no other way for these two expressions to be the same. Therefore, you can revise your wave function to be \[y(x) = B\cos(kx) \] now, there are two ways for y(L) = y(-L) = 0. First, B could be zero ... but that would be silly, because then our function would just be zero everywhere and that's not a good choice. The other possibility is for the cosine function to be zero. Now, you know that cos(x) = 0 at pi/2, 3pi/2, 5pi/2, etc... So this means that \[ kL = (2n-1)\frac{\pi}{2} \] where n = 1, 2, 3....... etc But this tells us what k may be. It appears that \[ k = \frac{(2n-1)\pi}{2L} \] so our wave function becomes \[y(x) = B\cos\left( \frac{(2n-1)\pi x}{2L}\right) \] And our allowed energies are \[E_n = \frac{\hbar^2 k^2}{2m} = \frac{(2n-1)^2 \pi^2 \hbar^2}{4mL^2}\] Our last step is to normalize our wavefunction -- that is, make sure that \[ \int_{-L}^L y_n(x)^2 dx = 1\] so we have \[\int_{-L}^L B^2 \cos^2\left(\frac{(2n-1)\pi x}{2L}\right) dx = B^2L = 1\] so \[B = \frac{1}{\sqrt{L}} \] and at long last, we have our completely normalized wavefunctions: \[ y_n(x) = \frac{1}{\sqrt{L}} \cos\left(\frac{(2n-1)\pi x}{2L} \right)\] and allowed energies: \[E_n = \frac{(2n-1)^2\pi^2 \hbar^2}{4mL^2} \] The ground state ( lowest energy) is n=1. n=2 is the first excited state, etc etc etc.

Looking for something else?

Not the answer you are looking for? Search for more explanations.